Penguatan Peran dan Fungsi Paralegal dalam Meningkatkan Akses Keadilan di Desa Deme Dua dan Desa Bubalango - Ibrahim Ahmad; Roy Marthen Moonti (Lembaga Pengembangan Kinerja Dosen, 2025)
Access to justice is a fundamental right that is still difficult to reach by rural communities, including in Deme Dua Village and Bubalango Village. Paralegals play an important role in providing legal assistance for people who have limited access to professional advocates. This study aims to analyze the strengthening of the role and function of paralegals in improving access to justice in the two villages. The research method used is a qualitative approach with a descriptive method to understand the dynamics of paralegals' roles in resolving legal disputes and the challenges they face. The results showed that paralegals contribute to legal education, conflict resolution through mediation, and legal assistance for vulnerable groups. However, they face obstacles such as limited resources and lack of recognition from the formal legal apparatus. In conclusion, strengthening the role of paralegals can improve access to inclusive justice in rural communities, but needs policy support and more systematic training.